2022
DOI: 10.1177/13506501221113161
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of wear and friction behaviour of AZ91D –B4C − Gr hybrid composite under dry sliding conditions

Abstract: The tribological behaviour of AZ91D magnesium alloy bottom pouring stir cast with boron carbide (B4C) and graphite (Gr) was examined. The wear and frictional properties of AZ91D magnesium alloy, AZ91D-B4C composite, and AZ91D-B4C-Gr hybrid composite were investigated individually under dry sliding circumstances. To perform the studies, the L9 orthogonal array approach was adopted to investigate the effects of various sliding distances (0.5, 1, and 2 km) and applied load (5, 10 and 20N). When compared to AZ91D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…They reported that the wear rate of samples increased from load of 10 to load of 60N. Murugesan et al [58] investigated the wear performance of AZ91/B 4 C-Gr composite and reported that the wear loss increased with increasing load. Ataya et al [64] investigated the wear behaviour of AZ91/SCF composites produced by squeeze casting.…”
Section: Applied Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that the wear rate of samples increased from load of 10 to load of 60N. Murugesan et al [58] investigated the wear performance of AZ91/B 4 C-Gr composite and reported that the wear loss increased with increasing load. Ataya et al [64] investigated the wear behaviour of AZ91/SCF composites produced by squeeze casting.…”
Section: Applied Loadmentioning
confidence: 99%
“…They reported that the asperities on the mating surfaces deformed with increasing load, causing to decrease in COF. Murugesan et al [58] investigated the effect of load and particle content on the COF values of the AZ91/B 4 C composites. They reported the COF decreased with increasing load.…”
Section: Analysis Of Cofmentioning
confidence: 99%